MERGERS AND ACQUISITIONS IN INTERNATIONAL BUSINESS - Nauman Zahid; Asif Mujtaba Shah (European Scientific Journal, ESJ, 2014)
Business is one of the oldest professions that mankind possesses, as time passed and with the advent of technology the earth seemed to squeeze, distances started to minimize, the age of globalization had begun. Businesses operating in different countries and continents could not confine them to a particular area and geography as it was not in line with globalization and it required things to be looked from a global perspective. Progressive businessmen always wanted to be ahead of their counterparts, this zeal of utilizing first mover advantage inspired mighty businessmen to opt for geographical expansions. Some of them did achieve this by going for mergers and acquisitions, which seems a smart move as one gets a running business. These mergers and acquisitions however can backfire as well and cannot prove to be a success story always. In the last decade, businesses from developing countries have started to buy out businesses of developed countries as their economies are doing better compared to the developed world due to low cost of production. Indian and Chinese businessmen are the most aggressive compared to rest in this regard.